ICOMI in Amapá: half a century of mining; A ICOMI no Amapá: meio século de exploraç\~ao mineral - Maurílio de Abreu Monteiro (Novos Cadernos NAEA, 2003)
This paper analyses the history of half a century of manganese ore mining in Serra do Navio, Amapá, Brazil, during the second half of the 20th century by the ICOMI (Indústria e Comércio de Minérios S.A.) company. The result is that mining provided limited internalization of the value added by mining. It also indicates that the existing bibliography on repercussions of this activity on regional development is less than satisfactory. This paper concludes by pointing to an open research agenda regarding the analysis of institutional arrangements that blocked or limited socially-grounded development in the region from the adding of value to manganese. – – O artigo analisa a história de meio século de exploraç\~ao do minério de manganês na Serra do Navio, Amapá, Brasil, na segunda metade do século XX, pela Indústria e Comércio de Minérios S.A. (ICOMI). Aponta que houve limitada internalizaç\~ao do valor adicionado pela mineraç\~ao. Indica que a bibliografia existente acerca das repercuss\~oes dessa atividade para o desenvolvimento regional n\~ao é satisfatória. Finaliza apontando que há uma agenda de pesquisa em aberto no que se refere à analise dos arranjos institucionais que bloquearam ou limitaram o enraizamento social do desenvolvimento na regi\~ao a partir da valorizaç\~ao do minerio de manganês.
Keywords: 330; Amazonia; Regional development; Bethlehem Steel; ICOMI; Pollution; Amapá